2020
DOI: 10.1186/s12936-020-03159-y
|View full text |Cite
|
Sign up to set email alerts
|

Extensive genetic diversity of Plasmodium vivax dbp-II in Rio de Janeiro Atlantic Forest and Brazilian Amazon Basin: evidence of positive selection

Abstract: Background: Plasmodium vivax is the most widespread human malaria parasite outside Africa and is the predominant parasite in the Americas. Increasing reports of P. vivax disease severity, together with the emergence of drugresistant strains, underscore the urgency of the development of vaccines against P. vivax. Polymorphisms on DBP-IIgene could act as an immune evasion mechanism and, consequently, limited the vaccine efficacy. This study aimed to investigate the pvdbp-II genetic diversity in two Brazilian reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
(30 reference statements)
2
9
0
Order By: Relevance
“…This constrained variation in terminal regions reinforces such protein structures importance for its interaction with Anopheles mosquito salivary gland and human hepatocytes during the invasion processes [52]. Conversely, CR diversity could reflect the host's immune system's evasion mechanism, as already observed for other surface antigens as pvdbp gene [12,68].…”
Section: Discussionsupporting
confidence: 67%
“…This constrained variation in terminal regions reinforces such protein structures importance for its interaction with Anopheles mosquito salivary gland and human hepatocytes during the invasion processes [52]. Conversely, CR diversity could reflect the host's immune system's evasion mechanism, as already observed for other surface antigens as pvdbp gene [12,68].…”
Section: Discussionsupporting
confidence: 67%
“…The most advanced P. vivax vaccine candidate to date is PvDBP-RII (268-513 aa.). The pvdbp gene has been show to exhibit high genetic diversity in Malaysia (π = 0.01000), Brazil (π = 0.01200) [45], and Myanmar (π = 0.00400-0.00600), as well as evidence of positive selection pressure [12,[46][47][48][49]. The PvDBP-RII fragment is a functional domain containing 12 conserved-cysteine residues, with a conserved protein structure and binding functions to DARC [50].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The PvDBP-II is highly polymorphic compared to the rest of the region. Genetic analysis from different geographical P. vivax isolates demonstrated that this region is under positive selection, with polymorphic residues varying by geographic region ( Ampudia et al, 1996 ; Xainli et al, 2000 ; Ju et al, 2013 ; Chootong et al, 2014 ; Almeida-de-Oliveira et al, 2020 ). Despite PvDBP-II presenting a promising vaccine antigenic, diversity may affect the immune recognition and host immune response which may reflect that polymorphisms of PvDBP-II help in immune evasion mechanism ( Cole-Tobian and King, 2003 ).…”
Section: Introductionmentioning
confidence: 99%